Thermogravimetry analysis, compressive strength and thermal conductivity tests of non-autoclaved aerated Portland cement-fly ash-silica fume concrete - Chalermphan Narattha (2018)
© 2015 Akadémiai Kiadó, Budapest, Hungary. This paper reports the investigated thermogravimetry analysis, compressive strength and thermal conductivity tests of non-autoclaved aerated Portland cement-fly ash-silica fume concrete. The mixes were cured in water and air for 3, 7 and 28 days. Thermogravimetry results showed that calcium silicate hydrate (C-S-H), ettringite, gehlenite (C < inf > 2 < /inf > ASH < inf > 8 < /inf > ), calcium hydroxide [Ca(OH) < inf > 2 < /inf > ] and calcium carbonate (CaCO < inf > 3 < /inf > ) phases were detected in all mixes. The compressive strength and thermal conductivity of aerated Portland cement-fly ash-silica fume concrete increased when compared with aerated Portland cement-fly ash concrete after 28 days. The compressive strength and thermal conductivity of aerated concrete cured in water had higher values than air-cured specimens. X-ray diffraction and thermogravimetry showed that Ca(OH) < inf > 2 < /inf > decreased with increased silica fume content. This is due to the increased pozzolanic reaction when compared with the Portland cement-fly ash mixes, which corresponds to an increase in compressive strength and thermal conductivity.